THE FIVE CONDITIONS OF ISLAM (Neo Scientific Peer Reviewed Journal, 2026)
The spread of Islam beyond Arabia is associated with the wars of conquest. They were ruled by Muhammad's successors, called caliphs (deputy prophets). The caliphs were the supreme rulers of the Arab Caliphate.